2009 3rd International Symposium on Empirical Software Engineering and Measurement 2009
DOI: 10.1109/esem.2009.5316044
|View full text |Cite
|
Sign up to set email alerts
|

Productivity trends in incremental and iterative software development

Abstract: In an investigating study to trace the productivity changes of a commercial software project, which uses incremental and iterative development model, we 've

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Inconsistencies have been noted in prior studies of software measurement data [4], [32], [39]. Tan et al [39] discovered inconsistencies when they studied a data set said to represent productivity trends in incremental and iterative software development.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistencies have been noted in prior studies of software measurement data [4], [32], [39]. Tan et al [39] discovered inconsistencies when they studied a data set said to represent productivity trends in incremental and iterative software development.…”
Section: )mentioning
confidence: 99%
“…Tan et al [39] discovered inconsistencies when they studied a data set said to represent productivity trends in incremental and iterative software development. These inconsistencies included size and effort data that did not match from report to report.…”
Section: )mentioning
confidence: 99%
“…Iterative software development methods are used by many organizations to reduce development risks and to deliver software projects on time [22,23]. Design and prototype testing are integral parts of the iterative implementation strategy.…”
Section: Iterative Implementation and Design And Prototype Testingmentioning
confidence: 99%
“…[ Maxwell et al, 1996, Tan et al, 2009 [ Boehm, 2000, Krishnan, 1998, Tan et al, 2009, Vosburgh et al, 1984 [Fenton and Pfleeger, 1997] Reuse. Several studies have found that reuse impacts positively on the productivity.…”
Section: Product Factorsmentioning
confidence: 99%
“…According to Tan et al [2009], software architecture drives productivity variation, since a well-planned and organized architecture tends to increase productivity. On the other hand, a deficient architecture will result in productivity decrease because of the needed re-architecting to bring the project back on track.…”
Section: Product Factorsmentioning
confidence: 99%